Influence Cooperative Learning Method and Personality Type to Ability to Write The Scientific Article (Experiment Study on SMAN 2 Students Ciamis Learning Indonesian Subject) - Supriatna Supriatna; Emzir Emzir; Yumna Rasyid (JETL (Journal of Education, Teaching and Learning), 2017)
The purpose of this research was to know the influence of cooperative learning method (Jigsaw and TPS) and personality type (extrovert and introvert) toward students’ ability in scientific writing at the SMA Negeri 2 Ciamis class XII. The research used experimental method with 2 x 2 factorial design. The population was the students of class XII which consisted of 150. The sample was 57 students. The results showed that: (1) The ability to write scientific articles of students learning by cooperative learning method jigsaw model (= 65,88) is higher than students who learn by cooperative technique method of TPS (= 59,88), (2) Ability writing scientific articles of students whose extroverted personality (= 65.69) is higher than introverted students (= 60.06); (3) there is interaction between cooperative learning method and personality type to score of writing ability of scientific article (4) ability to write scientific article of extrovert student and studying with technique of Jigsaw (= 77,75) higher than extrovert student learning with cooperative learning method model of TPS (= 53,63) to score of writing ability of scientific article, (5) ability to write introverted student's scientific article and get treatment of cooperative learning method of jigsaw model (= 54,00) lower than introverted student learning TPS technique = 66,13), (6) the ability to write extroverted students' scientific articles studied with jigsaw techniques, and introverted students who studied Jigsaw techniques (= 77.75) were higher than those with introverted personality types studied by the Jigsaw technique (= 54.00 ), (7) Ability to write scientific articles of students learning by cooperative techniques of TPS technique and have extrovert personality type ( = 53.63) lower than introverted students learning TPS techniques (= 66.13).